Incidencia del riesgo sistemático en la composición del índice Colcap en Colombia periodo 2014-2020 (2021)
This thesis analyzes the possible incidence of systematic risk in the composition of the COLCAP index in Colombia in the face of different conjunctural phenomena during the period between 2014 and 2020. Using the econometric model known as LOGIT and using as statistical information, a sample From 70 data where different descriptive economic variables were evaluated (price of the closing of the COLCAP index, Investments, exports and GDP), the analysis of the obtained results was carried out, thus evidencing a congruence between the theory and the model.